Testing the Neoclassical Theory of Economic Growth : A Panel Data Approach - Knight, Malcolm; Loayza, Norman; Villanueva, Delano (Washington, D.C. : International Monetary Fund, 1992)
Several recent empirical studies have examined determinants of economic growth using country average (cross-section) data. In contrast, this paper employs a technique for using a panel of both cross-section and time-series data for 98 industrial and developing countries over 1960-85 to determine the quantitative importance for economic growth of both country-specific and time-varying factors such as human capital, public investment, and outward-oriented trade policies. The empirical results provide support for the view that these factors exert a positive and significant influence on economic growth. They also provide estimates of the speed at which the gap in real per capita income between rich and poor countries is likely to be reduced over the longer term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet